If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -6 + -2x = 0 Reorder the terms: -6 + 10x + -2x = 0 Combine like terms: 10x + -2x = 8x -6 + 8x = 0 Solving -6 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 8x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 8x = 0 + 6 8x = 0 + 6 Combine like terms: 0 + 6 = 6 8x = 6 Divide each side by '8'. x = 0.75 Simplifying x = 0.75
| 3y+4x=-24 | | 10x-6x-x=0 | | (x^2)+8x+1= | | 10(x-5)=62 | | 8x-3x+2-x=4x+3 | | a^2+6=7a | | 2x^5+7x^4-10x^3-53x^2-28x+28=0 | | 10(x-5)=65 | | .5x+5=2x-17 | | k^2-14=-5k | | 65x+5=125 | | -16x^2+80x+32=0 | | -6+a= | | 1/2x+8= | | Y=x^2+52x+100 | | -2(5x-6)+17=1 | | 4x-4=21+x | | 3-3=7x+4x | | (1x+6)-(2x+7)-3x=9 | | W^2+2w-392=0 | | a^2-2a-3= | | 2+.075x=x | | 10x=15-3(x-3) | | -7=-3x^2-2x | | x^2-5x+8=-2 | | 12+5x=7(-6+8x)+3 | | 110=-2(-7r+1) | | 7x+(3x-6)= | | X^2-8x-4y+12=0 | | 3+-5x=54 | | 25xsquared+30x+9=0 | | 0=x^2+12x+20 |